Co-occurrence of snow leopard Panthera uncia, Siberian ibex Capra sibirica and livestock: potential relationships and effects. Issue 1 (4th March 2018) - Rovero, Francesco; Augugliaro, Claudio; Havmøller, Rasmus Worsøe; Groff, Claudio; Zimmermann, Fridolin; Oberosler, Valentina; Tenan, Simone
Abstract: Understanding the impact of livestock on native wildlife is of increasing conservation relevance. For the Vulnerable snow leopard Panthera uncia, wild prey reduction, intensifying human–wildlife conflicts and retaliatory killings are severe threats potentially exacerbated by the presence of livestock. Elucidating patterns of co-occurrence of snow leopards, wild ungulate prey, and livestock, can be used to assess the compatibility of pastoralism with conservation. We used camera trapping to study the interactions of livestock, Siberian ibex Capra sibirica and snow leopards in a national park in the Altai mountains, Mongolia. We obtained 494 detections of wild mammals and 912 of domestic ungulates, dogs and humans. Snow leopards and Siberian ibex were recorded 14 and 33 times, respectively. Co-occurrence modelling showed that livestock had a higher estimated occupancy (0.65) than ibex, whose occupancy was lower in the presence of livestock (0.11) than in its absence (0.34–0.35 depending on scenarios modelled). Snow leopard occupancy did not appear to be affected by the presence of livestock or ibex but the robustness of such inference was limited by uncertainty around the estimates. Although our sampling at presumed snow leopard passing sites may have led to fewer ibex detections, results indicate that livestock may displace wild ungulates, but may not directly affect the occurrence of snow leopards. Snow leopards could still be threatened by livestock, as overstocking can trigger human–carnivore conflicts and hamper the conservation of large carnivores. Further research is needed to assess the generality and strength of our results.